192 Men with Unusual Sexual Dysfunctions: A Novel Management Algorithm and Long-Term Treatment Outcome. Issue 1 (1st April 2022) - Goldstein, S.; Kim, C.; Blevins, J.; Uloko, M.; Komisaruk, B.; Kim, N.; Goldstein, I.
ABSTRACT: Introduction: The most commonly treated sexual dysfunctions in men are erectile dysfunction, Peyronie's disease, premature and delayed ejaculation, and decreased sexual desire. While urologists have expertise treating these sexual dysfunctions, there are unusual sexual health concerns in men that can prove a management quandary to many clinicians. These include persistent genital arousal, spontaneous ejaculation/orgasm, penile pain with arousal, and severe ejaculatory pain, which may be secondary to a radiculopathy of the sacral spinal nerve roots (SSNR). Men with these unusual problems often experience despair, emotional lability, catastrophization, and/or suicidality. Objective: The objective was to examine the management of men presenting to our multidisciplinary sexual medicine clinic with unusual sexual dysfunctions including persistent genital arousal, spontaneous ejaculation/orgasm, penile pain with arousal and severe ejaculatory pain, using a novel diagnostic and treatment algorithm. Methods: We performed a retrospective chart review of men who presented to our clinic from 2015 through 2020 with a history of an unusual sexual dysfunction lasting for more than 3 months and had, at minimum, a follow-up of one year post treatment. All were managed using the novel algorithm, which included a sex therapy evaluation, neurogenital sensory testing of both the pudendal and sciatic nerves, measurement of the bulbocavernosus reflex latency, regional dorsal and pudendal nerve diagnostic anesthesia testing, lumbosacral MRI, and diagnostic transforaminal epidural spinal injection (TFESI) with an anesthetic. If the unusual sexual dysfunction was suspected to be secondary to SSNR radiculopathy, lumbar endoscopic spine surgery (LESS) was performed. Results: Five patients (mean age at presentation 26, range 17 – 38 years) meeting the criteria had the following symptoms: persistent genital arousal (3/5), distressing penile pain with arousal (3/5), spontaneous ejaculation/orgasm (2/5), and/or severe ejaculatory pain (2/5). Significant psychological distress was noted including suicidal ideation in 3/5 of patients. Neurogenital testing was abnormal in all. Mean perception of finger/glans vibration, cold and heat were 4/11 volts; 21.2/15.8° and 31 /37° respectively. Mean perception of finger/buttock vibration, posterior thighs and posterior calf were 4/14.3 volts. Mean value of bulbocavernosus reflex latency testing was 93 msec (normal 30-50 msec). Regional dorsal and pudendal nerve diagnostic anesthesia tests failed to temporarily resolve unusual sexual dysfunction symptoms in 100%. MRI findings showed annular tears in 5/5: L5-S1 (2/5), L4-L5 (4/5). Diagnostic TFESI resulted in clinically significant symptom reduction in 5/5. Based on these results, sexual dysfunctions were highly suspected to be secondary to SSNR radiculopathy. All patients underwent LESS, were discharged the same day, and had no surgical complications. All reported improvement on Patient Global Impression of Improvement of very much better (2/5) or much better (3/5). Mean follow-up was 21.6 months post-LESS treatment. Conclusions: Unusual sexual dysfunctions can be a management challenge to urologists. Although persistent genital arousal, spontaneous ejaculation/orgasm, penile pain with arousal, and severe ejaculatory pain are perceived to be in the genitals, in this patient population these unusual sexual dysfunctions were actually caused by an upstream mechanical/inflammatory SSNR radiculopathy from lumbosacral annular tears. Symptom alleviation was achieved by LESS in all patients. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Elliquence, Lumenis